Unfolding the Epistemological Meanings and Pedagogical Implications of Geography Textbook Questions - Mishra, Rishabh Kumar (JOURNAL OF INDIAN EDUCATION, 2014)
Textbook questions and exercises are quintessential part of every textbook. One can easily locate textbook questions at the end of the every chapter and also in between the text. What are they meant for? Usually we think they are meant for assessing learners’ understanding regarding subject knowledge, providing clue to teacher to form other questions. However, besides these popular notions, textbook questions implicitly communicate messages about what is ‘worth’ knowledge and what learning is about? The present paper takes geography textbook questions as a unit of analysis and tries to analyse the nature of textbook questions with reference to content and cognitive processes perspective.